Identifying critical steps towards improved access to innovation in cancer care: a European CanCer Organisation position paper. (September 2017) - Aapro, Matti; Astier, Alain; Audisio, Riccardo; Banks, Ian; Bedossa, Pierre; Brain, Etienne; Cameron, David; Casali, Paolo; Chiti, Arturo; De Mattos-Arruda, Leticia; Kelly, Daniel; Lacombe, Denis; et al.
Abstract: In recent decades cancer care has seen improvements in the speed and accuracy of diagnostic procedures; the effectiveness of surgery, radiation therapy and medical treatments; the power of information technology; and the development of multidisciplinary, specialist-led approaches to care. Such innovations are essential if we are to continue improving the lives of cancer patients across Europe despite financial pressures on our healthcare systems. Investment in innovation must be balanced with the need to ensure the sustainability of healthcare budgets, and all health professionals have a responsibility to help achieve this balance. It requires scrutiny of the way care is delivered; we must be ready to discontinue practices or interventions that are inefficient, and prioritise innovations that may deliver the best outcomes possible for patients within the limits of available resources. Decisions on innovations should take into account their long-term impact on patient outcomes and costs, not just their immediate costs. Adopting a culture of innovation requires a multidisciplinary team approach, with the patient at the centre and an integral part of the team. It must take a whole-system and whole-patient perspective on cancer care and be guided by high-quality real-world data, including outcomes relevant to the patient and actual costs of care; this accurately reflects the impact of any innovation in clinical practice. The European CanCer Organisation is committed to working with its member societies, patient organisations and the cancer community at large to find sustainable ways to identify and integrate the most meaningful innovations into all aspects of cancer care. Highlights: Innovation in cancer care does not have to be complex or expensive. An innovation's value depends on patient outcomes, quality of life and system costs. A whole-system, whole-patient approach is required to guide investment in innovation. Patients must be more involved in defining and assessing the value of innovation. Investment in real-world data is essential to shape decisions about interventions.